1987
DOI: 10.1029/jb092ib05p03507
|View full text |Cite
|
Sign up to set email alerts
|

Temporal change in coda associated with the Round Valley, California, Earthquake of November 23, 1984

Abstract: Seven thousand seismograms of small earthquakes in the Mammoth Lakes‐Bishop area were used to measure values of Q from the decay of the earthquake coda. These measurements were compared between events that occurred before and after the Round Valley earthquake (M=5.7). We found that in regions near the main shock epicenter, measurements of coda Q−1 for earthquakes that occurred after the main shock were higher than for those earthquakes that occurred prior to the main shock. The opposite behavior was found for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The low Q belt also follows the focal area of the 1967 Mudurnu Valley earthquake. The observation that after a strong earthquake the Q-value drops has been made by other seismologists too (Peng et al 1987).…”
Section: Composite Fault-plane Solutionsmentioning
confidence: 96%
“…The low Q belt also follows the focal area of the 1967 Mudurnu Valley earthquake. The observation that after a strong earthquake the Q-value drops has been made by other seismologists too (Peng et al 1987).…”
Section: Composite Fault-plane Solutionsmentioning
confidence: 96%
“…Several studies reported decreases in Q-' value associated with earthquake occurrences (e.g., Jin and Aki, 1986;Sato, 1987;Peng et al, 1987). On the contrary, increases in Qc-1 value associated with earthquakes also have been obtained (e.g., Tsukuda, 1988;Peng et al, 1987). Precursory increases of Qc-1 value with earthquake occurrences have been reported by Gusev and Lemzikov (1985) and Jin and Aki (1986).…”
Section: Temporal Changementioning
confidence: 99%
“…strongly depends on the location of hypocenter and the time window. Several studies reported decreases in Q-' value associated with earthquake occurrences (e.g., Jin and Aki, 1986;Sato, 1987;Peng et al, 1987). On the contrary, increases in Qc-1 value associated with earthquakes also have been obtained (e.g., Tsukuda, 1988;Peng et al, 1987).…”
Section: Temporal Changementioning
confidence: 99%
“…Since then, a great number of studies on the attenuation of coda waves have been carried out applying the single-scattering model, for numerous regions in the world (e.g., Roecker et al, 1982;Pulli, 1984;Pujades et al, 1990;Canas et al, 1991). Although there are more general models (e.g., Gao et al, 1983;Wu and Aki, 1988;Frankel and Wennerberg, 1987;Zeng et al, 1991), their use and application is less extended, due, in part, to the complexity of the mathematical expressions or to the instability of the numerical solutions (Peng et al, 1987).…”
Section: Introductionmentioning
confidence: 99%